2014
DOI: 10.1371/journal.pone.0110037
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of Fatigue after First-Ever Ischemic Stroke during Acute Phase

Abstract: Background and PurposeFatigue after stroke is common and has a negative impact on rehabilitation and survival. However, its pathogenesis and contributing factors remain unclear. The purpose of this study was to identify factors influencing the occurrence of fatigue after first-ever ischemic stroke in acute phase.MethodsWe examined 265 consecutive patients with first-ever ischemic stroke during acute phase (within 2 weeks) in two tertiary stroke care hospitals in Henan, China. We documented patients’ demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 30 publications
3
59
1
3
Order By: Relevance
“…While many of the previous studies that investigated the determinants of PSF have reported conflicting and inconclusive findings, the impact of level of functional ability (or disability) appears be fairly consistent across studies (4,15,17,22,23). A recent systematic review of PSF literature showed that 25 studies found a significant association between PSF and functional ability while 15 studies did not (4).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…While many of the previous studies that investigated the determinants of PSF have reported conflicting and inconclusive findings, the impact of level of functional ability (or disability) appears be fairly consistent across studies (4,15,17,22,23). A recent systematic review of PSF literature showed that 25 studies found a significant association between PSF and functional ability while 15 studies did not (4).…”
Section: Discussionmentioning
confidence: 97%
“…While findings are largely conflicting and apparently inconclusive (9), some studies have shown significant associations between PSF and demographic factors such as female gender (10-12) and older age (10,11,13). Similarly, there is some evidence that clinical factors such as functional ability and pre-stroke fatigue influence PSF (3,4,14,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2015) menjelaskan prevalensi tertinggi fatigue pada pasien post stroke bisa terjadi pada bulan ke tiga setelah serangan hal ini dikaitkan dengan umur dan jenis kelamin. Studi lain kejadian fatigue dapat terjadi selama fase akut (2 minggu) pada pasien post stroke iskemik dan hal ini dikaitkan dengan depresi, aktivitas sebelum stroke dan disfungsi keluarga (Wang, et al, 2014).…”
Section: Pendahuluanunclassified
“…Epidemiological survey results in recent years have demonstrated that cerebrovascular disease accounts for the second highest mortality rates in China, second only to malignant tumors (2). As for the survivors, ~75% of patients with cerebrovascular disease lose the capacity to work, to varying degrees and >40% may be severely disabled (3,4). Therefore, cerebrovascular disease is associated with high morbidity and mortality, causing serious harm to human health and quality of life.…”
Section: Introductionmentioning
confidence: 99%